2021
DOI: 10.1080/09669760.2021.1948820
|View full text |Cite
|
Sign up to set email alerts
|

Nordic preschool student teachers’ views on early writing in preschool

Abstract: This study investigates preschool student teachers' views on how early writing should be supported in preschool. The sample consists of 66 preschool student teachers from Finland, Norway, and Sweden, who participated in the study by responding to open-ended questions on a written questionnaire. Results show that the respondents' answers were underpinned by holistic views on children's learning; they value children's own initiative as a decisive learning factor. Further, the responses underscore the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In contrast to this perspective, research also identifies that teachers believe that young children find writing to be interesting (Gerde et al, 2019b) and that they identify young children as writers early on (Hall et al, 2019;Magnusson et al, 2022). For example, Hall et al (2019) found that early educators had more positive beliefs about preschoolers' writing abilities than parents, demonstrating an understanding of writing development that was not typical of other adults.…”
Section: Early Writing Beliefs and Practicesmentioning
confidence: 94%
See 3 more Smart Citations
“…In contrast to this perspective, research also identifies that teachers believe that young children find writing to be interesting (Gerde et al, 2019b) and that they identify young children as writers early on (Hall et al, 2019;Magnusson et al, 2022). For example, Hall et al (2019) found that early educators had more positive beliefs about preschoolers' writing abilities than parents, demonstrating an understanding of writing development that was not typical of other adults.…”
Section: Early Writing Beliefs and Practicesmentioning
confidence: 94%
“…Perhaps this is why we observe ample opportunities for children to write their name with a range of materials, opportunities for tracing and copying letters, and experiences for exercising fine motor skills available at writing centers (Gerde et al, 2015). This readiness perspective is not unusual among early childhood educators and may be how those beliefs and ideas are manifested for early writing through the provision of writing materials and activities (Gerde et al, 2019b;Magnusson et al, 2022).…”
Section: Variability Of Teachers' Beliefs and Ideas About Writingmentioning
confidence: 97%
See 2 more Smart Citations